The localized reduced basis multiscale method - Albrecht, Felix; Haasdonk, Bernard; Kaulmann, Sven; Ohlberger, Mario (Proceedings of the Conference Algoritmy, 2015)
In this paper we introduce the Localized Reduced Basis Multiscale (LRBMS) method for parameter dependent heterogeneous elliptic multiscale problems. The LRBMS method brings together ideas from both Reduced Basis methods to eciently solve parametrized problems and from multiscale methods in order to deal with complex heterogeneities and large domains. Experiments on 2D and real world 3D data demonstrate the performance of the approach.